Multi-dimensional, transparent and foldable cellulose-based triboelectric nanogenerator for touching password recognition. (July 2022) - Xu, Shuhan; Zhao, Huiqi; Li, Qing; Zhang, Renyun; Gao, Sen; Wang, Fei; Li, Guoliang; Chen, Bailing; Yu, Haipeng; Liu, Shouxin; Li, Jian; Chen, Wenshuai; et al.
Abstract: Transparent power sources are required for emerging electronics and energy devices. However, most transparent materials/systems present certain problems: they are often fragile and unsuitable for shaping into fixed three-dimensional structures. Here, we attempted to overcome these challenges by constructing a cellulose-based multilayer film as a single-electrode triboelectric nanogenerator (TENG). The TENG was simply fabricated by the step-by-step deposition of a cellulose triboelectric layer, a silver nanowire electrode layer, and a protective cellulose layer. The tightly packed thin film is transparent, flexible and foldable. Four TENGs were spontaneously assembled into one film, and various spatial configurations were generated by a series of cutting and folding processes. We proved the practicality of a TENG-containing cellulose-based multilayer film by developing a multi-dimensional touch password switch, and expect that it will be widely used in film-based intelligent electronics. Graphical Abstract: Cellulose-based multilayer film was constructed as single-electrode triboelectric nanogenerator, which was fabricated by step-by-step deposition of a cellulose triboelectric layer, a silver nanowire electrode layer, and a cellulose protective layer. The as-produced film was transparent, conductive, flexible, and foldable. It could be shaped into various spatial structures such as single-plane, two-plane, three-plane, and complex configurations by simply cutting and folding. The cellulose-based multilayer film was used as a touch switch for a portable concealment electronic device. Password recognition and unlocking were accomplished by touching the triboelectric nanogenerators in a specific sequence. ga1 Highlights: We propose a strategy to develop transparent and foldable cellulose-based single-electrode triboelectric nanogenerator. Four TENGs were assembled in one piece of film, and various spatial configurations were fabricated by cutting and folding. Concealment touching password switch was realized simply by finger touching the film at various spatial positions.